2015
DOI: 10.1016/j.ijsolstr.2014.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Micromechanical modeling of the elastic behavior of unidirectional CVI SiC/SiC composites

Abstract: International audienceThe elastic behavior of SiC/SiC composite is investigated at the scale of the tow through a micromechanical modeling taking into account the heterogeneous nature of the microstructure. The paper focuses on the sensitivity of transverse properties to the residual porosity resulting from the matrix infiltration process. The full analysis is presented stepwise, starting from the microstructural characterization to the study of the impact of pore shape and volume fraction. Various Volume Elem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 55 publications
0
28
0
Order By: Relevance
“…[Castelier et al (2010)] showed that the three families of models tend to provide identical results as the composite become very long. All these modeling principles have been defined for the case of a microcomposite (containing a single fiber) and they are directly extended to minicomposites, neglecting the propagation of the matrix crack through the section of the minicomposite (despite experimentally observed [Chateau et al (2011)]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[Castelier et al (2010)] showed that the three families of models tend to provide identical results as the composite become very long. All these modeling principles have been defined for the case of a microcomposite (containing a single fiber) and they are directly extended to minicomposites, neglecting the propagation of the matrix crack through the section of the minicomposite (despite experimentally observed [Chateau et al (2011)]).…”
Section: Introductionmentioning
confidence: 99%
“…First, some 1D models [Lissart and Lamon (1997), ] used the classical fiber bundle assumptions (developed by [Daniels (1945)]) according to which once broken, a fiber does not participate anymore to the load transfer throughout the whole composite, and as a consequence breaks only once. However, a fiber break characterization in SiC/SiC minicomposites (detailed in [Chateau et al (2011)]) recently showed that a fiber can break several times. So observations are rather in line with other family of approaches taking into account a sliding length around a break necessary for the fiber to recover back its previously carried stress.…”
Section: Introductionmentioning
confidence: 99%
“…GPa and Poisson's ratio of 0.2 (values similar to those used in [56]). This is a reasonable assumption as long as the mechanical behavior remains in the elastic regime, for the following reasons.…”
Section: Unit Cell Generationmentioning
confidence: 99%
“…Firstly, both SiC fibers and matrix are commonly considered as isotropic materials (see e.g. [16,56]). Although the SiC matrix exhibits an anisotropy resulting from the CVI process, the elastic modulus of -SiC varies moderately in different crystallographic directions (face-centered cubic system), hence the assumption of isotropic elastic property of SiC matrix can be admitted (Chapter 3 in [57]).…”
Section: Unit Cell Generationmentioning
confidence: 99%
See 1 more Smart Citation